Reverse logistics of medicines in Brazil: environmental and legal impacts - Milkievicz, Indianara Ignacio; Borges, Catiane Rosa; Paes, Eduarda Sutil Medeiros; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues (Revista DELOS, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista DELOS (e-ISSN: 1988-5245) ON 2025-03-25, AVAILABLE ONLINE: https://doi.org/10.55905/rdelosv18.n65-115 Abstract Pharmaceutical waste management in Brazil faces significant challenges, and reverse logistics is a promising tool to address this situation. One of the main obstacles is the lack of awareness among the population regarding the proper disposal of medicines, which leads to inappropriate practices that compromise both public health and the environment. Incorrect disposal has severe environmental impacts, including ecosystem contamination and increased resistance to pathogens, underscoring the urgent need for responsible disposal methods. Although legislation, such as Law No. 12.305/2010, exists, its effective enforcement remains limited, especially in the North and Northeast regions, where the collection infrastructure is insufficient. In this context, education and awareness campaigns are crucial for the success of reverse logistics. Programs that foster partnerships between governments and non-governmental organizations have shown positive results. The study suggests improvement strategies, including expanding the collection network, launching intensive educational campaigns, and offering financial incentives to companies involved in reverse logistics. These findings underline the importance of an integrated approach that combines public awareness, strong public policies, and adequate infrastructure to achieve a safer and more sustainable future in pharmaceutical waste management.
Keywords: Reverse logistics; Pharmaceutical waste; Proper disposal; Awareness; Public health; LAW/JURISPRUDENCE::Other law::Environmental law